Physical characteristics of photon and electron beams from a radiotherapy accelerator - C., Varatharaj; B, Shwetha; Reddy B, Rekha; M., Ravikumar; S., Sathiyan; K.M., Ganesh (International Journal of Medical Research and Review, 2016)
Introduction: Radiotherapy uses high-energy radiation to shrink tumors and kill cancer cells. The radiation may be delivered by a machine outside the body (external-beam radiation therapy), or it may come from radioactive material placed in the body near cancer cells (brachytherapy). Many types of external-beam radiation therapy are delivered using a machine called a linear accelerator (also called a LINAC). The process of commissioning a linac for clinical use includes comprehensive measurements of dosimetric parameters that are necessary to validate the treatment planning systems used to select optimal radiation modality and treatment technique for individual patients. In the present study, clinically pertinent data for both the available photon and electron energies were investigated. Methods: For making measurements in water, a three dimensional radiation field analyzer RFA-300 (Scanditronix Wellhofer) and for absolute dosimetry and other measurements like relative output factors, wedge factors etc., a DOSE1 electrometer (Scanditronix Wellhofer) in a white polystyrene were employed. Results: The percentage depth dose data, wedge factors, output factors and cross beam profiles have been measured and compared with the other studies for photon beams and isodose plots, virtual source to surface distance, uniformity index for electron beams. Conclusion: All these measured data were utilized as input to the ECLIPSE treatment planning system for further clinical use. The characteristics of the electron beams are found to follow the trends experimentally observed by others, generally found to be different from the others theoretically predicted and depend on the model of the machine.